F. A. Hayek and the Economic Calculus - Bruce Caldwell (Duke University, Center for the History of Political Economy (CHOPE), 2015)
The paper offers a revisionist account of certain episodes in the development of F. A. Hayek's thought. It offers a new reading of his 1937 paper, "Economics and Knowledge," that draws on unpublished lecture notes in which he articulated more fully the distinctions he made in the paper between a "pure logic of choice," or the economic calculus, and an "empirical element," which he would later call the competitive market order. Next, the paper shows that Hayek continued to try to develop his ideas about the role of the economic calculus through the 1950s and early 1960s, an effort that has been missed because it never led to any published work. Finally, the paper examines Hayek's attempt to articulate a theory of the market process, one that would be at the same level of generality as the economic calculus, in lectures he gave at the University of Virginia. He never developed a full - fledged formal theory, but his failed efforts still bore fruit in leading him to his contributions on spontaneous orders and the (verbal) theory of complex phenomena. This work anticipated contributions by others who were more technically trained.
Keywords: 330; F. A. Hayek; economic calculus; market process; pure logic of choice; structure of economic theory; spontaneous orders